Ramp Study Hemodynamics, Functional Capacity, and Outcome in Heart Failure Patients with Continuous-Flow Left Ventricular Assist Devices. Issue 4 (July 2016) - Jung, Mette H.; Gustafsson, Finn; Houston, Brian; Russell, Stuart D.
Abstract : Ramp studies—measuring changes in cardiac parameters as a function of serial pump speed changes (revolutions per minute [rpm])—are increasingly used to evaluate function and malfunction of continuous-flow left ventricular assist devices (CF-LVADs). We hypothesized that ramp studies can predict functional capacity, quality of life (QOL), and survival in CF-LVAD patients. Hemodynamic changes per Δrpm were measured at a minimum of CF-LVAD support, at baseline pump speed, and at maximal tolerable pump speed. Subsequently functional capacity and QOL were assessed. Eighty ramp tests were performed in 44 patients (HeartMate II, Thoratec Corporation, Pleasanton, CA). Functional status was evaluated in 70% (31/44); average 6 minute walk test (6MWT) was 312 ± 220 min, New York Heart Association (NYHA) I–II/III–IV (70/30%) and activity scores very low–low/moderate–very high (55/45%). Decrease in pulmonary capillary wedge pressure per Δrpm was related to better NYHA classification; NYHA I–II vs. III–IV, −0.29 ± 0.15 vs. −0.09 ± 0.16 mm Hg/rpm * 10 −2 ( p = 0.007) as well as to activity score; very low–low vs. moderate–very high, −0.16 ± 0.16 vs. −0.31 ± 0.16 mm Hg/rpm * 10 −2 ( p = 0.02). Cardiac output change per Δrpm was correlated to measures of QOL. Ramp tests did not predict survival. In conclusion, hemodynamic changes during ramp studies are associated with measures of functional capacity and QOL. Hence, such tests could potentially identify patients in risk of failure to thrive during CF-LVAD support.